Molecular genetics of the Peninsular Malaysian termite genus Odontotermes - Cheng, Shawn (2011)
Termites of the genus Odontotermes (Macrotermitinae) are important decomposers in the Old World tropics. Species within the genus have overlapping size ranges and are difficult to differentiate based on morphology. As a result, the taxonomy of species within the genus is poorly resolved. In this study, the species boundaries of the Peninsular Malaysian Odontotermes were elucidated using mtDNA genes, namely the 16S ribosomal RNA and cytochrome oxidase subunit I. MtDNA genes defined at least eleven species of Odontotermes in Peninsular Malaysia, namely, o. escherichi, O. hainanensis, O. javanicus, O. longignathus, o. malaccensis, O. oblongatus, O. paraoblongatus, o. sara waken sis, and three morphospecies that have now been identified as O. azmiensis sp. nov, O. minutus and O. srinakarinensis sp. nov. Microsatellite markers were also developed de novo to investigate the presence of cryptic species in O. srinakarinensis sp. nov, a clade which consisted of samples with highly divergent sequences. Shared allele trees, principal components analysis and Bayesian clustering of genotype data from 191 termite individuals from this species complex showed that samples in this clade were in fact made up of two species, that is, O. srinakarinensis and O. denticulatus. This was corroborated by morphological and distributional differences between these species. After mtDNA and microsatellite data helped elucidate the species boundaries of the Peninsular Malaysian Odontotermes, the soldiers of each species were morphometrically characterised. In addition, information on the host and habitat associations of species within the Odontotermes, and their distribution throughout the peninsula were determined.